The Development of Electrolysis Cell Teaching Material based on STEM-PjBL Approach Assisted by Learning Video: A Need Analysis - Widarti, H. R.; Rokhim, D. A.; Syafruddin, A. B. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2020)
This study attempts to explore teachers’ and students’ needs on the development of electrolysis cell teaching materials assisted by a learning video. Data were obtained through open question questionnaires and close-ended questions given to 15 teachers and 15 students of senior high school in East Java province. What teachers need of interactive learning media is both in knowledge and thinking skills and adds insight to students’ conceptual understanding. Besides, it can apply 4C skills (Communication, Collaboration, Critical Thinking, Problem Solving, Creativity, and Innovation). Chemistry learning materials that students want are interactive instructional video media integrated with information technology. The level of teacher and student confidence in learning chemistry in schools on the topic of voltaic cells was carried out based on STEM-PjBL education assisted by learning videos of 78.6 and 89.2. Therefore, it is necessary to develop teaching materials with appropriate approaches and methods that can support chemistry learning on the topic of electrolysis cells in the form of STEM-PjBL-based textbooks assisted by learning videos featuring triple representative.